Preserved Fronto-Striatal Plasticity and Enhanced Procedural Learning in a Transgenic Mouse Model of Alzheimer's Disease Overexpressing Mutant hAPPswe - Middei, Silvia (Cold Spring Harbor Laboratory Press, 2004)
Mutations in the amyloid precursor protein (APP) gene inducing abnormal processing and deposition of β-amyloid protein in the brain have been implicated in the pathogenesis of Alzheimer's disease (AD). Although Tg2576 mice with the Swedish mutation (hAPPswe) exhibit age-related Aβ-plaque formation in brain regions like the hippocampus, the amygdala, and the cortex, these mice show a rather specific deficit in hippocampal-dependent learning and memory tasks. In view of recent findings showing that neural systems subserving different forms of learning are not simply independent but that depressing or enhancing one system affects learning in another system, we decided to investigate fronto-striatal synaptic plasticity and related procedural learning in these mutants. Fronto-striatal long-term depression (LTD) induced by tetanic stimulation of the cortico-striatal input was similar in Tg2576 and wild-type control mice. Behavioral data, however, pointed to an enhancement of procedural learning in the mutants that showed robust motor-based learning in the cross maze and higher active avoidance scores. Thus, in this mouse model of AD, an intact striatal function associated with an impaired hippocampal function seems to provide neural conditions favorable to procedural learning. Our results suggest that focusing on preserved or enhanced forms of learning in AD patients might be of interest to describe the functional reorganization of the brain when one memory system is selectively compromised by neurological disease.